Sikap Warga Desa Ekowisata Pancoh terhadap Partisipasi Perempuan Pemilik Usaha Pariwisata Berdasarkan Pengukuran Women Owned Operated Tourism Businesses (WOOTB) - Anindwitya Rizqi Monica (Gadjah Mada Journal of Tourism Studies, 2018)
This research aimed to understand resident’s attitudes toward women participation in tourism businesses especially understanding potential impacts-based Women Owned and Operated Tourism Businesses (WOOTB) measurement. This research is being held in Pancoh Ecotourism Village, Turi, Sleman, Yogyakarta Special Region, Indonesia. WOOTB measurement created by Beedle (2011) through quantitative method. WOOTB is measured by six components. The components are tourism impact, tourism enhancement, economic enhancement, capacity building, community structure, and tourist contact. This measurement will seek for total score of each items from six components of WOOTB interpreted by scale that have been done by Umar (2001). By collecting the data from 100 residents from 15 – 64 years old, both who are involved and non-involved in tourism activities in Pancoh Ecotourism Village, the result shows that there are di erent attitudes from the residents. The di erence shown from the average of total score in tourism impact component, economic enhancement component, and community structure component. Other than that, there is a similarity from the component of capacity building and tourism enhancement that revealed both high average to the statement by involved and non-involved residents. Meanwhile, in the component of tourism contact about “Women owned businesses in Pancoh would result in too much contact between local women and foreign tourists” revealed a low average to the statement both from involved and non-involved residents in Pancoh Ecotourism Village.